If \(log_a x\) = p and \(log_b {x^2}\) = q then \(log_x \sqrt{ab}\) is equal to

Solution :

\(log_a x\) = p \(\implies\) \(a^p\) = x \(\implies\) a = \(x^{1/p}\)

Similarly  \(b^q\) = \(x^2\) \(\implies\) b = \(x^{2/q}\)

Now, \(log_x \sqrt{ab}\) = \(log_x \sqrt{x^{1/p}x^{2/q}}\) = \(log_x x^{({1\over p}+{2\over q}){1\over 2}}\) = \(1\over {2p}\) + \(1\over q\).


Similar Questions

Solve for x : \(2^{x + 2}\) > \(({1\over 4})^{1\over x}\).

Evaluate the given log : \(81^{l\over {log_5 3}}\) + \(27^{log_9 36}\) + \(3^{4\over {log_7 9}}\).

Find the value of \(2log{2\over 5}\) + \(3log{25\over 8}\) – \(log{625\over 128}\).

If \(log_e x\) – \(log_e y\) = a, \(log_e y\) – \(log_e z\) = b & \(log_e z\) – \(log_e x\) = c, then find the value of \(({x\over y})^{b-c}\) \(\times\) \(({y\over z})^{c-a}\) \(\times\) \(({z\over x})^{a-b}\).

Leave a Comment

Your email address will not be published.